Website-Based Management of School Committee Institutional Development Contributions - Fatkhurrochman, Fatkhurrochman; Kapti, Kapti; Yusnanto, Tri; Febriani, Yeza; Muin, Muhammad Abdul (Institut Teknologi Bisnis AAS Indonesia, 2024)
One form of community participation in providing education is the formation of a School Committee. The School Committee acts as an independent body that accommodates and places the community's initiative aspirations in forming school policies and school programs in the education unit. Likewise with the School Committee at SMP Negeri 1 Kaloran. The School Committee is given the authority to manage Institutional Development Contributions from students. Currently, the management of institutional development donations still uses manual methods which still poses several risks in managing this data. This research aims to develop a website-based school committee institutional development donation management information system using the CodeIgniter framework by applying the waterfall method in developing the system. To design the system, the UML method is used with use case diagrams and class diagrams as an illustration of system design. Meanwhile, in system testing, the black box testing method with a Likert scale is used to determine the feasibility of the implemented system. The system was successfully implemented with system test results of 90.33%. This shows that the system is feasible to implement and has met user needs.